Perceived Effectiveness of Antismoking Ads and Association with Quit Attempts Among Smokers: Evidence from the Tips From Former Smokers Campaign. Issue 8 (3rd August 2017) - Davis, Kevin C.; Duke, Jennifer; Shafer, Paul; Patel, Deesha; Rodes, Robert; Beistle, Diane
ABSTRACT: Background . Measures of perceived effectiveness (PE) of ads have been validated to predict changes in cognitive precursors of quit attempts, but a relationship between PE and actual quit attempts has not been shown in population-based studies. We analyzed smokers' PE ratings of ads from the national Tips From Former Smokers ( Tips ) campaign to (1) establish the validity of PE in predicting quit attempts in a large, nationally representative sample of smokers; (2) identify behavioral and demographic correlates of PE among respondents; and (3) examine whether PE is influenced by matching the race/ethnicity of ad participants with that of the ad viewer.Methods . We used survey data from two waves (baseline and follow-up) of a longitudinal online cohort of adult U.S. cigarette smokers. Respondents were shown one or more of 14 Tips campaign ads and were asked to assess each ad in terms of PE. We used multivariate models to estimate the association between baseline PE and prospective quit attempts; cross-sectional associations between PE and various respondent characteristics, including race/ethnicity, desire to quit, and health conditions; and the association between race/ethnicity of respondents and Tips ad participants.Results . Higher PE at baseline was associated with increased odds of a quit attempt at follow-up. Higher PE scores were associated with non-Hispanic black race, Hispanic ethnicity, higher desire to quit, presence of a chronic health condition, and presence of a mental health condition. There was no relationship between PE scores and matched race/ethnicity of the respondent and Tips ad participants.Conclusions . This is the first study to demonstrate an association between PE scores for antismoking ads and prospective quit attempts in a large, nationally representative sample of smokers. Our findings also provide strong evidence that racial/ethnic minority subpopulations, including non-Hispanic blacks and Hispanics, react more favorably to Tips campaign ads irrespective of race/ethnicity of the ad participant. This suggests that message characteristics (e.g., graphic visuals and emotional content) may play a more important role in PE than race/ethnicity of ad participants.